2019
DOI: 10.3390/rs11182136
|View full text |Cite
|
Sign up to set email alerts
|

New ECOSTRESS and MODIS Land Surface Temperature Data Reveal Fine-Scale Heat Vulnerability in Cities: A Case Study for Los Angeles County, California

Abstract: Rapid 21st century urbanization combined with anthropogenic climate warming are significantly increasing heat-related health threats in cities worldwide. In Los Angeles (LA), increasing trends in extreme heat are expected to intensify and exacerbate the urban heat island effect, leading to greater health risks for vulnerable populations. Partnerships between city policymakers and scientists are becoming more important as the need to provide data-driven recommendations for sustainability and mitigation efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 138 publications
1
36
1
Order By: Relevance
“…The intercomparison of multiple cities in this work suggests that a single direction of influence cannot be generalized; however, generally, H resulted in a weak or negative contribution to high daytime LST. This study also supports previous qualitative findings observing that the high-rise urban core was not the warmer part of the city by day: In Vancouver [112], Paris [113], Shanghai [20], Phoenix [114], London [115], and Los Angeles [116]. Finally, in [117], it was demonstrated that in several cases worldwide, LCZ 1-corresponding to neighborhoods with the higher building heights-had lower LST compared to other LCZ classes with similar building density but lower height.…”
Section: Discussionsupporting
confidence: 90%
“…The intercomparison of multiple cities in this work suggests that a single direction of influence cannot be generalized; however, generally, H resulted in a weak or negative contribution to high daytime LST. This study also supports previous qualitative findings observing that the high-rise urban core was not the warmer part of the city by day: In Vancouver [112], Paris [113], Shanghai [20], Phoenix [114], London [115], and Los Angeles [116]. Finally, in [117], it was demonstrated that in several cases worldwide, LCZ 1-corresponding to neighborhoods with the higher building heights-had lower LST compared to other LCZ classes with similar building density but lower height.…”
Section: Discussionsupporting
confidence: 90%
“…After Zhang [ 8 ] and Hulley [ 17 ], the heat risk index was constructed by the multiplication of heat hazard, heat exposure, and heat vulnerability, and the HVI index was obtained according to the formula below. HVI = Exposure index (E) + Sensibility index (S) − Adaptability index (A) …”
Section: Methodsmentioning
confidence: 99%
“…Impaired workers' health can lead to a decline in human productivity and economic loss [50]; adaptation and preventive measures are needed for these working groups. The literature has shown that apparent temperatures are reliable for assessing the working environment [51], but most heat assessment research studies only consider air temperature and land surface temperature [12,17,52]. In this situation, this study introduced wet bulb globe temperature (WBGT) as an indicator in heat risk assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, a spatial resolution below 100 m is required for mapping at scale useful for urban applications (Sobrino, Oltra-Carrió, Sòria, Bianchi, & Paganini, 2012). ECOSTRESS on JAXA JEM the and a future DIEGO sensor on Bartolomeo are therefore well suited for this application as they allow to implement multispectral temperature/emissivity separation approaches, such as the TES (Gillespie et al, 1998), for retrieving most accurate LST (Hulley, Shivers, Wetherley, & Cudd, 2019) at high spatial resolution.…”
Section: The Diego Sensor Designmentioning
confidence: 99%